1974
DOI: 10.1111/j.1537-2995.1974.tb04567.x
|View full text |Cite
|
Sign up to set email alerts
|

Experiences with Frozen Erythrocytes in a Private Hospital

Abstract: Frozen erythrocytes can provide a valuable addition to many blood banks for better patient care. Exaggerated fears concerning cost and complexity have frightened many blood bankers from consideration of a frozen erythrocyte program for their hospital blood bank. This type of program promotes improved blood banking as it emphasizes the need for increased utilization of specific blood components in hemotherapy. Since better inventory control is achieved, the patient is more likely to receive the desired componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1976
1976
1993
1993

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The potential role of frozen RBC in the prevention of post-transfusion hepati tis was first suggested by Tullis et al [16], but, although he found no case of hepatitis after transfusion of frozen red cells, the number of cases in the control group was consid ered too small for the data to be conclusive. Other retro spective clinical reports suggested a beneficial effect [11,12,27,28]. In contrast, Alter et al [29] showed that hu man red cells dosed with HBV could still transmit hepati tis B to chimpanzees after freezing.…”
Section: Discussionmentioning
confidence: 91%
“…The potential role of frozen RBC in the prevention of post-transfusion hepati tis was first suggested by Tullis et al [16], but, although he found no case of hepatitis after transfusion of frozen red cells, the number of cases in the control group was consid ered too small for the data to be conclusive. Other retro spective clinical reports suggested a beneficial effect [11,12,27,28]. In contrast, Alter et al [29] showed that hu man red cells dosed with HBV could still transmit hepati tis B to chimpanzees after freezing.…”
Section: Discussionmentioning
confidence: 91%